Implementation of The CTL Learning Model Through Islamic Moderate Values in Improving the Attitude of Students Tolerance in School - Ja'far Amirudin; Uus Ruswandi; Mohamad Erihadiana; Elis Rohimah (Nazhruna: Jurnal Pendidikan Islam, 2022)
This study aims to describe the application of the Contextual Teaching and Learning (CTL) model through the values of Islamic moderation in increasing the tolerance attitude of students in Indonesia. The type of research used in this study is a literature study or literature review. The data used in this study are from the results of research that has been carried out and published in national and international online journals. The application of the CTL model through Islamic moderation values will provide students with the independence to identify Islamic moderation values that are rooted in the values of life in the family or in the community. In addition, the Contextual Teaching and Learning (CTL) approach instills Islamic moderation values directly through habituation by participating in community activities that are able to foster an attitude of tolerance and cooperation.